Book Review: Improving Reading Comprehension of Middle and High School Students (Journal of School Administration Research and Development, 2016)
This highly readable volume should be required reading for all middle and high school teachers across all content areas. Education administrators and those who provide education and professional development for teachers should also find it quite useful. Parents will also find the information valuable and clearly presented. The overviews of relevant research in each chapter are succinct and helpful information for class- room implementation. The volume, with its impres- sive cadre of contributors, represents a crucial contri- bution to moving the information learned over recent decades into practice. Reed and Santi have done an admirable job of achieving their goal of providing re- search-based evidence on adolescent literacy learning that moves toward a blending of general and special education and better learning gains for all students, including those with learning disabilities.